Women’s Participation In Waste Management (Case Studyin Dau District, Malang Regency) - Kresnapratiwi, Rahajeng Galuh Imansari; Sholihah, Hidayatus (Sekolah Pascasarjana Universitas Brawijaya, 2024)
Community participation manifests public awareness, concern, and responsibility for the importance of development, which aims to improve the quality of life. Development is the government's obligation and demands community involvement, whose quality will be improved. Indonesia, in carrying out environmental development, still really needs community participation in terms of waste management. Waste management aims to improve public health, environmental quality, and economic resources. This waste management activity will contribute to the government by creating job opportunities, improving welfare, and empowering women who do not work. This study analyzed women's participation in waste management in Dau District, Malang Regency. Respondents were 28 women who became administrators of the Family Welfare Program in the sub-district. To measure the level of participation, the number of scores from the variables was then calculated in the rating scale. The results showed that women's participation in waste management was at the placation level, namely the 5th level of the 8 participation levels. The research suggestion is to increase women's participation through empowerment, namely giving women greater decision-making in the waste management cycle, starting from planning, implementing, monitoring, and evaluating. Keywords: Waste management, women’s participation, women’s empowerment